Stress Analysis on Emergency Pipeline from Flare to Pressure Vessel - Lukitadi, Projek Priyonggo Sumangun; Setiawan, Priyo A.; Ramadani, Tarikh A.; Mulya, Mirza Z. I. (Institut Teknologi Sepuluh Nopember, 2025)
This work focuses on the analysis of emergency piping systems connected to flares and pressure vessels at oil and gas facilities in West Papua. The main objective is to determine support placement, and analyze pipe stress on flares and pressure vessels. The methods used include calculating the maximum allowable pipe span, stress analysis based on ASME B31.3. The results of the research show that a 6 in emergency pipe line requires a minimum of 2 supports with a maximum allowable pipe span of 36.967 ft. The pipe flexibility value of 0.00146 is still below the limit of 0.02582 set by ASME B31.3. Stress analysis due to sustained, occasional, and thermal expansion loading shows the highest values respectively of 2572.5 lb/in² (12.6% of the permit limit), 1294.0 lb/in² (18.9% of the permit limit for seismic loads), 595.0 lb/in² (2.2% of the permit limit for wind loads), and 23921.3 lb/in² (49.3% of the permit limit).